Pencatatan Perkawinan Campuran Beda Agama Berdasarkan Hukum Kanonik dan Hukum Positif - Kwirinus, Dismas (Kamaya: Jurnal Ilmu Agama, 2024)
The focus of this research examines the registration of mixed religious marriages based on canon law and positive law. The topic of study is related to the legal instruments governing mixed religious marriages, the implementation of mixed religious marriages based on Church law and positive law. The aim of this study is to serve as a guideline for government agencies that have firm authority regarding marriage and everything related to marriage. Researchers used descriptive qualitative methods and critical reading of texts, namely: (1) Canon Law 1124-1129; (2) Law Number 1 of 1974 article 2 paragraph (1) in conjunction with article 66; (3) Law Number 23 of 2006. The results and findings in this research are that interfaith marriages can be obtained and registered with the Civil Registry Officer and obtain a Deed and Excerpt from the Marriage Certificate, requiring first a decision from the court as regulated in article 35 Law no. 23 of 2006. Meanwhile, marriages issued by the Catholic Church do not receive enough Marriage Certificate Excerpts from the Population and Civil Registration Service. The conclusion from this research is that the implementation of a Mixed Mexta Religio marriage must first obtain a license from the Church authorities, because the marriage is a prohibited marriage. It is seen as a prohibition because there are many elements of similarity and togetherness between the Christian and Catholic Churches. Meanwhile, Marriage Disparity Cultus is seen as an obstacle to marriage (impedimentum disparity cultus) and to confirm this marriage a dispensation is needed.